Peningkatan Kompetensi Kepemimpinan Perawat dalam Pengelolaan Pelayanan Keperawatan melalui Pelatihan Leadership Berbasis Praktik Klinis - Solehudin Solehudin; Inas Syabanasyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Leadership competence is one of the essential competencies that nurses must possess to effectively manage nursing services and improve the quality of patient care. However, many nurses still encounter challenges in decision-making, communication, team management, and problem-solving within clinical settings. Therefore, leadership training based on clinical practice is needed to strengthen nurses' leadership capacity. This community service program aimed to improve nurses' leadership competencies in nursing service management through clinical practice-based leadership training. The program was conducted using a participatory approach involving 40 nurses from a regional hospital. Activities included needs assessment, preparation, implementation of leadership training, simulation, case discussions, mentoring, and evaluation. Participants' knowledge was measured using pre-test and post-test assessments. The average pre-test score was 63.5, which increased to 86.8 in the post-test, indicating an improvement of 23.3 points. Participants demonstrated enhanced understanding of transformational leadership, effective communication, conflict management, delegation, and clinical decision-making. Increased confidence and leadership initiative were also observed among participants. Clinical practice-based leadership training effectively improved nurses' leadership competencies in managing nursing services. Similar programs should be implemented regularly to support professional nursing development and healthcare service quality improvement.